Design Variation, Implantation, and Outcome of Transcatheter Mitral Valve Prosthesis: A Comprehensive Review - Sazzad, Faizus; Hon, Jimmy Kim Fatt; Ramanathan, Kollengode; Nah, Jie Hui; Ong, Zhi Xian; Ti, Lian Kah; Foo, Roger; Tay, Edgar; Kofidis, Theo (Frontiers in Cardiovascular Medicine, 2022)
Transcatheter mitral valve prosthesis is ideally suited for patients with inoperable mitral etiology. Transcatheter mitral valve replacement (TMVR) procedure has closely followed the evolution of transcatheter aortic procedures. There are considerable design variations amongst the limited TMVR prostheses currently available and the implantation profile of the devices are notably different. This comprehensive review will provide a current overview of the current clinically tried TMVR devices, with a focused outcome analysis. In addition, we have discussed the various design characteristics of TMVR and its associated failure mode, implantation technology, delivery methods, first-in-man trials and pivotal trial summary for synthesis of current evidence.